Tax harmonization in the European Community : Policy Issues and Analysis - Kopits, George (Occasional Papers; Occasional Paper ;, 1992)
Tax harmonization is an integral part of completing the single European market. Expansion of the single market to the European Economic Area, and eventually to some Eastern European countries, suggests that the EC approach to tax harmonization will apply more broadly than origninally envisaged. This study considers these issues and examines the case for harmonizing taxation of commodities and capital income in the single European market; principles of international taxation; the impact of harmonizing value-added taxes; and EC Structural Funds.